Kantakuzin-Speransky's project of 1891 on reforming of spiritual affairs management of the Crimean Tatars - I.K. Zagidullin (Ученые записки Казанского университета: Серия Гуманитарные науки)
The reasons and prerequisites of drawing up the project on reforming of the spiritual affairs management of the Crimean Tatars in 1891 by M.R. Kantakuzin-Speransky, the head of the Department of Spiritual Affairs of Foreign Confessions of the Ministry of Internal Affairs, were analyzed. The principles of the reform realization were considered. Its basic provisions were covered. It was noted that the project was created and influenced by the conservative nationalism of Alexander III’s rule aimed to reduce the size of the clergy institution and to establish complete government control over it and the Taurian Mohammedan spiritual board with subsequent integration of the Islamic institutes into the Russian administrative legal framework. Interestingly, the complex revision of the spiritual affairs management of the Crimean Tatars was not highly prioritized by the state and, therefore, the Ministry decided to realize step by step only some most relevant articles of the project. Following the sudden death of M.R. Kantakuzin-Speransky, the plans were dropped. Another reason for holding up the realization of the measures was the social behavior of the Crimean Tatars who were political loyal to the political regime of that time.